PENINGKATAN DAYA SAING USAHA MELALUI PERBAIKAN KEMASAN DAN PEMASARAN - Sanusi; Larisang; M. Ansyar Bora (LPPM Universitas Ibnu Sina, 2022)
SMEs (Small and Medium Enterprises) play a very important role in advancing the Indonesian economy, especially in the city of Batam. Apart from being an alternative for new employment opportunities, SMEs also play a role in boosting the pace of economic growth after the 1997 monetary crisis, when large companies experienced difficulties in developing their businesses. The MSME segment in Riau Islands Province is also high where more than 60,000 MSMEs or 3.0% of the total population of the province, higher than the national MSME share which was only 1.6% in 2012. The highest distribution composition is in Batam, which is 67%. , followed by Tanjung Pinang 19%, Natuna 5%, and Bintan 3%. In addition, Batam is also an area directly adjacent to neighboring countries such as Singapore and Malaysia as well as being the center of tourist destinations for both local and foreign tourists. So this provides a great opportunity for SMEs to sell processed products that will be used as souvenirs or souvenirs for tourists. Increasing competitiveness can be done by improving packaging and marketing that pays attention to environmental and social aspects. Technological developments and increasing knowledge of prospective customers in the future. The training provided provides understanding and interest for business actors in developing their businesses and improving skills and understanding of science and technology.